FILSAFAT MATEMATIKA: KEDUDUKAN, PERAN, DAN PERSEPEKTIF PERMASALAHAN DALAM PEMBELAJARAN MATEMATIKA - Yosua Damas Sadewo; Pebria Dheni Purnasari; Suyitno Muslim (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
This research aims to provide a detailed study of the philosophy of mathematics, the relation of the philosophy of mathematics with learning, anduncover problems in the study of mathematics from the perspective of mathematical philosophy. The research method used is a qualitative researchmethod with a review literature approach to surveying several articles about mathematical philosophy and problems in mathematics learning. Basedon the research results, it can be concluded that the philosophy of mathematics is a reflection of the science of mathematics itself and affirms themeaning of truth in mathematics. The scope in the philosophy of mathematics can be categorized into four branches of science, namely mathematicalepistemology, mathematical ontology, mathematical methodology, and mathematical logic. The implementation of learning consisting of inputs,processes, and outputs cannot be separated from the role and position of mathematical philosophy. Obstacles in the performance of education can becaused by the unconnected part of the philosophy of mathematics in the learning process.